СТРУКТУРНІ ОСОБЛИВОСТІ СПІВАЦЬКОГО НАВЧАННЯ СТУДЕНТІВ ІНСТИТУТІВ МИСТЕЦТВ З ВИКОРИСТАННЯМ ІННОВАЦІЙНИХ ТЕХНОЛОГІЙ - Даофен, Сі (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкритті структурні особливості співацького навчання майбутніх учителів музики. Розроблена компонентна структура, критерії оцінювання, показники та рівні результатів співацького навчання майбутніх учителів музики, а саме: мотиваційно-спрямований, технологічно-компетентнісний, креативно-діяльнісний компоненти. У цій структурі мотиваційно-спрямований компонент забезпечує стабільний інтерес до співацької діяльності, активізацію, цілеспрямованість і ефективність навчання. Технологічно-компетентнісний компонент розкриває обсяг ерудиції в різних видах співочої діяльності, забезпечує комплекс професійних знань необхідних для шкільної практики майбутніх учителів музики. Креативно-діяльнісний компонент передбачає готовність майбутнього вчителя музики до творчого використання інноваційних технологій у співацькій діяльності, прояв творчої активності в практичній роботі. Обґрунтовано науково-теоретичні основи використання інноваційних технологій у процесі вокального навчання майбутнього вчителя музики, що розкривають своєрідність цього феномена, його спрямованість на творчу самореалізацію особистості й рефлексивне осмислення процесу й результатів співацької діяльності. В статье раскрываются структурные особенности певческого обучения будущих учителей музыки. Разработана компонентная структура, критерии оценки, показатели и уровни результатов певческого обучения будущих учителей музыки, а именно: мотивационно-направленный, технологически-компетентностный, креативно-деятельный компоненты. В этой структуре мотивационно-направленный компонент обеспечивает стабильный интерес к певческой деятельности, активизацию, целеустре-мленность и эффективность обучения. Технологически-компетентностный компонент раскрывает объем эрудиции в различных видах певческой деятельности, обеспечивает комплекс профессиональных знаний необходимых для школьной практики будущих учителей музыки. Креативно-деятельный компонент предусматривает готовность будущего учителя музыки к творческому использованию инновационных технологий в певческой деятельности, проявление творческой активности в практической работе. Обоснованны научно-теоретические основы использования инновационных технологий в процессе вокального обучения будущего учителя музыки, раскрывающих своеобразие этого феномена, его направленность на творческую самореализацию личности и рефлексивное осмысление процесса и результатов певческой деятельности. The article revealing the structural features singers training future music teachers. Designed component structure, criteria, indicators and results level singers training future music teachers, namely motivational aims, technologically-competency, creative-activity components. In this structure, motivational and directional component provides a stable interest of singers, activation, commitment and effectiveness studies. Technologically-competency component disclose the amount of scholarship in various forms of singing, provides a range of professional skills necessary for school practice of future teachers of music. Creative-activity component involves the readiness of the future teacher of music the creative use of innovative technologies of the singers, the manifestation of creative activity in practice. A scientific-theoretical foundations of the use of innovative technology in vocal and choral music training future teachers, revealing the uniqueness of this phenomenon, its focus on the creative self-identity and reflexive thinking process and results of singers. Methods singers training future music teachers using innovative technologies consisted of three stages. The first stage - cognitive-adaptive included: adaptation of students for the new academic requirements, understanding the mentality of singing, search through the effective use of innovative technologies singing training. The second stage - reflexive-depth, which held the assimilation of different songbirds knowledge and skills; familiarization with musical fragments multimedia games and music programs; forming installation on improving professional knowledge. The third stage - analytical and creative aims at awareness of students features singing, creative transformation of this knowledge in practice.